Elimination of cervical cancer in Latin America (Project ECHO-ELA): lessons from phase one of implementation - Schmeler, Kathleen M (2023)
Fil: Schmeler, Kathleen M. University of Texas MD Anderson Cancer Center Houston United States of America The University of Texas MD Anderson Cancer Center; Estados Unidos.